Spatial Analysis of Dengue Hemorrhagic Fever Case Distribution in West Java Province 2023 - Sufiyana Jannatin, Illa; Yuniar, Popy (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Introduction: Dengue Hemorrhagic Fever (DHF) is a communicable disease that poses a significant public health challenge in Indonesia. Research Objectives: This study aims to spatially analyze Dengue Hemorrhagic Fever (DHF) case distribution in West Java Province in 2023 using Incidence Rate (IR) and Case Fatality Rate (CFR) variables. Materials and Method: Data were obtained from the West Java Health Profile and the Central Bureau of Statistics, processed using Quantum GIS software. Research Results: The analysis results indicate that areas with high vulnerability to Dengue Hemorrhagic Fever (DHF) are predominantly urban regions, such as Bogor City, Sukabumi City, and Bandung City. Conclusions: This spatial visualization is expected to serve as a reference for policymakers in designing more effective Dengue Hemorrhagic Fever (DHF) control and prevention strategies. GIS-based information also facilitates a better understanding of health phenomena for readers.